Multifaceted impact of shape coexistence in proton-rich nuclei within a beyond-mean-field model - Petrovici Alexandrina; Andrei Oana (EPJ Web of Conferences)
The proton-rich medium mass nuclei bring insights into fundamental symmetries and interactions. Exotic behavior manifested by the appearance of isomeric states, their feeding by the β decay of the neighboring nuclei as well as their complex decay are strongly influenced by shape coexistence and mixing. Aiming to a comprehensive description of different coexistence phenomena we investigated the structure and dynamics of nuclei close to N=Z line in the frame of the beyond-mean-field complex Excited Vampir model using an effective interaction derived from a G-matrix based on the Bonn CD potential. Results concerning the impact of shape coexistence on the structure and dynamics of exotic nuclei will be discussed and compared with recent experimental data.